An object-oriented toolkit for music notation - Eales, Andrew Arnold (Rhodes University, Faculty of Science, Department of Computer Science, 1999)
This thesis investigates the design and implementation of an object-oriented toolkit for music notation. It considers whether object-oriented technology provides features that are desirable for representing music notation. The ability to sympathetically represent the conventions of music notation provides software tools that are flexible to use, and easily extended to represent less common features of music notation. The design and implementation of an object-oriented class hierarchy that captures the structural and semantic relationships of music notation symbols is described. Functions that search for symbols, and update symbol positions are also implemented. Traditional context-sensitive and spatial relationships between music symbols may be maintained, or extended to provide notational features found in modern music. MIDI functionality includes the ability to play music notation and to allow step-recording of MIDI events. The toolkit has been designed to simplify the creation of applications that make use of music notation; example applications are created to demonstrate its capabilities.,Microsoft Word,Adobe Acrobat 9.46 Paper Capture Plug-in
Keywords: Musical notation; Object-oriented programming (Computer science); Computer music -- History and criticism; Musical notation -- Software